Derogating obese individuals: the role of blame, contempt, and disgust. Issue 4 (1st November 2015) - Wirtz, Coen; van der Pligt, Joop; Doosje, Bertjan
Abstract: Weight stigma is pervasive and has profound negative consequences for obese individuals. The attribution‐emotion approach of stigmatization holds that blame attributions relate to derogation stigmatized groups indirectly through anger and pity. Other research suggests that disgust is related to weight stigma. In the present studies, we investigate whether contempt is a reliable predictor of biases against obese individuals. Study 1 ( N = 297) shows that contempt partially mediates the relation between blame and both prejudice and support for weight related discrimination policies. Studies 2 and 3 (total N = 406) added disgust and show that both contempt and disgust relate to social distance and prejudice. Contempt mediated the relation between blame and negative reactions toward obese individuals, even after controlling for other emotions, while disgust only mediated these relations in Study 2. Anger and pity did not show this mediating role, but pity was moderately associated with weight bias. Contempt is likely to play an important role in how people react to members of this stigmatized group.